Electrocatalytic Carbohydrate Oxidation with 4-Benzoyloxy-TEMPO Heterogenised in a Polymer of Intrinsic Microporosity. (1st April 2015) - Kolodziej, Adam; Ahn, Sunyhik D.; Carta, Mariolino; Malpass-Evans, Richard; McKeown, Neil B.; Chapman, Robert S.L.; Bull, Steven D.; Marken, Frank
Graphical abstract: Abstract: The enzymeless and operationally simple electrocatalytic oxidation of carbohydrates by "heterogenised" 4-benzoyloxy-TEMPO either (i) immobilised as microcrystals at a glassy carbon electrode surface or (ii) embedded into a polymer of intrinsic microporosity (PIM-EA-TB with 1027 m 2 g −1 BET surface area and highly rigid framework structure) has been studied in aqueous phosphate buffer of pH 12. It is shown that in contrast to microcrystal deposits, 4-benzolyoxy-TEMPO co-immobilised within PIM-EA-TB give stable catalytic responses for both, stationary and rotating disc electrode systems and for oxidation of glucose, sorbitol, and sucrose. The rigidity and intrinsic microporosity of PIM-EA-TB allow (slow) substrate and product diffusion, whilst maintaining 4-benzoyloxy-TEMPO immobilised in active molecular form.